Metabolic engineering of essential oil yield and composition in mint by altering expression of deoxyxylulose phosphate reductoisomerase and menthofuran synthase - Mahmoud, Soheil S. (The National Academy of Sciences, 2001)
Peppermint (Mentha × piperita L.) was independently transformed with a homologous sense version of the 1-deoxy-d-xylulose-5-phosphate reductoisomerase cDNA and with a homologous antisense version of the menthofuran synthase cDNA, both driven by the CaMV 35S promoter. Two groups of transgenic plants were regenerated in the reductoisomerase experiments, one of which remained normal in appearance and development; another was deficient in chlorophyll production and grew slowly. Transgenic plants of normal appearance and growth habit expressed the reductoisomerase transgene strongly and constitutively, as determined by RNA blot analysis and direct enzyme assay, and these plants accumulated substantially more essential oil (about 50% yield increase) without change in monoterpene composition compared with wild-type. Chlorophyll-deficient plants did not afford detectable reductoisomerase mRNA or enzyme activity and yielded less essential oil than did wild-type plants, indicating cosuppression of the reductoisomerase gene. Plants transformed with the antisense version of the menthofuran synthase cDNA were normal in appearance but produced less than half of this undesirable monoterpene oil component than did wild-type mint grown under unstressed or stressed conditions. These experiments demonstrate that essential oil quantity and quality can be regulated by metabolic engineering. Thus, alteration of the committed step of the mevalonate-independent pathway for supply of terpenoid precursors improves flux through the pathway that leads to increased monoterpene production, and antisense manipulation of a selected downstream monoterpene biosynthetic step leads to improved oil composition.